Modelo teórico comprensivo de la vivencia del bullying en víctimas y agresores a partir del juego de rol (RPG). Un estudio de niños y niñas entre 7 y 9 años de nivel socioeconómico alto y bajo en Barranquilla ﻿ (2012)
The objective of this work is to understand the daily living of bullying in kids, victims and aggressors, using the Role play game (R.P.G) and taking into account the theoric methodologic aspects of the established theory. 25 boys and girls from schools of high and low social economical levels from Barranquilla participated in this investigation. The process of codification let us build the different conceptual categories with content the main elements about the bullying lived for the participants involved. The results show that victims identified themselves as wild animals and they constantly show behaviors of scape. However, when they feel frustrated they act aggressively and they usually justify their behavior changing it for weak aggressions actions. The aggressors usually identify themselves as strong and predator’s beings, showing the higher number of aggressive behaviors and, at the same time, the higher number strong physical aggressions. Generally, these kids attack first, an offense is not necessary for them to do it. Differences were found related to the gender so that aggressor –girls identify themselves with the most beautiful and cute animals, prey or predators meanings are not important for them. Usually girls did not use physical aggressions instead they apply more psychological aggressions and assertive behaviors than males.